What is good Urbanism? - Ellin, Nan (Journal of Architecture and Urbanism, 2013)
Across the globe, we are currently undergoing a paradigm shift that is fostering a felicitous turn in urban design, place-making, and community building. This “good urbanism” begins with appreciative inquiry and engages in meaningful co-creation, enabling us to envision best possibilities and rally resources to realize them. Good urbanism adds a few instruments to our planning and design toolkits that enhance the health and well-being of places and move beyond sustainability to prosperity.